Corporate Social Responsibility, Koneksi Politik, dan Intensitas Modal: Peran Profitabilitas dalam Agresivitas Pajak - Abi Rekrian Dwi Cahya; Riyan Harbi Valdiansyah (Jurnal Akuntansi dan Keuangan, 2026)
This study examines the effect of Corporate Social Responsibility (CSR), political connections, and capital intensity on tax aggressiveness, with profitability as a moderating variable, in food and beverage companies listed on the Indonesia Stock Exchange during 2020–2024. Using purposive sampling, 12 companies were selected, yielding 60 observations analyzed through panel data regression with the Random Effect Model (REM). Tax aggressiveness was measured by the Effective Tax Rate (ETR). Results show that political connections have a significant negative effect, capital intensity a significant positive effect, while CSR has no effect. Profitability strengthens the influence of political connections but does not moderate CSR or capital intensity. These findings imply that tax aggressiveness in the food and beverage sector is driven more by capital structure and political ties than social activities. Policymakers should tighten oversight of fixed asset transactions and politically affiliated firms, while future research may explore other moderating factors such as corporate governance or industry competition.